Development of Augmented Reality (AR) Learning Media to Increase Student Motivation and Learning Outcomes in Science - Yusa, Ilham Widia; Wulandari, Ana Yuniasti Retno; Tamam, Badrud; Rosidi, Irsad; Yasir, Mochammad; Setiawan, Achmad Yusuf Bagus (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
This research aims to 1) develop AR learning media regarding the interaction of living things and the environment, 2) determine the feasibility and response to AR media, and 3) determine differences in students' motivation and science learning outcomes before and after implementing AR media. AR-based mobile application. The study of AR media development uses the Waterfall development model which consists of 5 stages, namely analysis, design, code, testing, and maintenance. In-depth research data collection techniques use observation sheets, interview guides, media expert and material expert validation questionnaires, student response questionnaires as well as science learning motivation questionnaires and cognitive tests. The learning trial used a quasi-experimental design method with a research pattern using a nonequivalent control group pretest and posttest design involving 2 classes, namely class VII-C as the control group and VII-D as the experimental group. The results of the research show that 1) AR-based mobile applications can be used anytime and anywhere, the resulting applications are equipped with animations, games, and 3-dimensional and 2-dimensional images, 2) the product is valid and AR-based AR-based mobile applications are suiTabel for testing and response results in students towards AR-based mobile applications received a very good response from students, 3) learning using AR-based mobile applications can increase learning motivation and student learning outcomes, especially in the subject of interaction between living things and the environment.